PENGARUH PEMASARAN MEDIA SOSIAL DAN PROMOSI PENJUALAN DENGAN AKUN INSTAGRAM TERHADAP MINAT BELI KONSUMEN ALFAMART DI DKI JAKARTA - Raihan Hilmi (2023)
The digitization of the economy is one of the efforts made by many sectors to survive in society, one of which is using social media with various features presented. Social media platform is often used by retail companies in Indonesia, such as Alfamart. This research is aimed at knowing, analyzing, and proving the effect of social media marketing and sales promotion on purchase intention. This research uses quantitative methods with primary data collection. Data was collected using a non-probability sampling technique with a purposive sampling method. Questionnaires were distributed to 100 respondents via Google Form who fulfill the criteria which had seen Alfamart's Instagram account, and domiciled in DKI Jakarta. The data analysis techniques used descriptive and inferential analysis using the SmartPLS 3.0 application. The results show that social media marketing using Instagram accounts has no significant effect on purchase intention with a path coefficient value of 0.137, meanwhile sales promotions using Instagram accounts have a significant effect on purchase intention with a path coefficient value of 0.681. Meanwhile, social media marketing and sales promotion together contributed 60.70%, while the remaining 39.30% was caused by other factors. Therefore it is necessary to evaluate social media marketing so that its use is more effective. In other hand, sales promotion needs to be developed so that its effect remains in a stable manner to support increased consumer buying interest.